Edupark Textbook on Physics of Hot Water Semurup in Kerinci Jambi, Indonesia in terms of the depth of the material and the application of the scientific approach according to the 2013 curriculum for SMA / MA - Yuni Wulandari; - Hamdi; - Akmam; Wahyuni Satria Dewi (PILLAR OF PHYSICS EDUCATION, 2021)
The depth of the material is how detailed the concepts that exist in a learning material. Learning with a scientific approach is learning that is designed in such a way with the steps of observe, asking questions, gathering information, associating, and communicating. The research objective was to determine the level of application of a scientific approach and material depth based on the 2013 curriculum for SMA / MA with this type of research, namely descriptive research with a qualitative approach. The population in this study was the Edupark Physics book, a master's thesis development research. For standard books, namely Physics textbooks used in West Sumatra, Indonesia. The samples of this study were Physics textbooks Edupark Semurup Kerinci Hot Water and standard books, namely physics book class XI SMA / MA by Muhammad Farchani Rosyid, et al. The data were taken using research instruments and data analysis techniques in the form of analysis sheets The results showed that the depth of material in the Edupark book was higher, namely 79.87% compared to the MFR book which was 66.30% and both of them had the appropriate category. Meanwhile, the results of the application of the scientific approach to the Edupark textbook were 34.84% lower than the MFR book, which was 39.07%, but they had the same category, which was not suitable. Can show that the Edupark Hot Water Semurup Kerinci textbook material depth is higher than the standard book. And for the application of the scientific approach, Edupark's book is still a lot of subject matter that has not applied the steps of the scientific approach.